1983
DOI: 10.1159/000241637
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Dopamine in Developing Swine

Abstract: Cardiac function and peripheral blood flows were measured before and during single intravenous injections of dopamine (2–25 μg/kg) in developing and mature swine anesthetized with pentobarbital. A positive inotropic effect was observed in even the youngest swine. Renal vasoconstriction was observed even after low doses of dopamine in animals younger than 1 month of age, and femoral vasoconstriction in animals younger than 2 weeks of age, unless α-adrenergic receptors were blocked by phentolamine. We concluded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…These observations support the theory of Gootman el a/. (40,41) and others (42) that in the postnatal period, vascular autonomic receptors mature at different rates (40), with the or adrenergic receptor being mature at birth, but the "dopaminergic" receptor requiring significant postnatal development.…”
Section: Effects Of Dopumine Infusionsupporting
confidence: 85%
“…These observations support the theory of Gootman el a/. (40,41) and others (42) that in the postnatal period, vascular autonomic receptors mature at different rates (40), with the or adrenergic receptor being mature at birth, but the "dopaminergic" receptor requiring significant postnatal development.…”
Section: Effects Of Dopumine Infusionsupporting
confidence: 85%
“…Interestingly, the renal response to low-dose dopamine is age dependent in animals. This is interpreted as a maturation process of renal dopamine receptors (6)(7)(8). However, premature neonates with respiratory distress syndrome receiving 2 pg/kg/min of dopamine increased their natriuresis compared to a matched control group not treated by dopamine (28).…”
Section: Discussionmentioning
confidence: 99%
“…A considerable amount of data supports its use in adults (1-5) but hemodynamic and renal effect of dopamine have not yet been assessed in children. Some animal (6)(7)(8) and clinical studies (9) suggest that differences in response to dopamine exist between adults and pediatric patients.…”
mentioning
confidence: 99%
“…Renal vasoconstriction was noted in young swine, whereas vasodilatation occurred in older animals after a-and P-adrenergic receptor blockade. Bucky et al (16) observed renal vasoconstriction in swine younger than 1 month even after a single, low, intravenous dose of dopamine unless a-adrenergic receptors were blocked by phentolamine. In addition, they evaluated the regional circulatory effects of dopamine infused into developing swine and suggested that the developmental time course of dopamine receptors differed from the particular regional circulation (1 7).…”
Section: Discussionmentioning
confidence: 99%